2015
DOI: 10.4103/2278-330x.149949
|View full text |Cite
|
Sign up to set email alerts
|

Role of FNAC in Hepatic lesions: Risk of track metastases

Abstract: Background:Liver is one of the most common site of metastases in patients with malignancy and the evaluation of space occupying lesions (SOL) of liver in patients with malignancy is important. Its important to differentiate benign from malignant to take necessary decisions.Materials and Methods:We have performed a retrospective analysis of liver SOLs for which fine needle aspiration cytology (FNAC) was done in the year 2011. Risks and benefits associated with FNAC were evaluated.Results:We analyzed 755 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
4
9
1
Order By: Relevance
“…19 A report of Reddy et al, has reported low PPV of 58.8%. 12 These values are contrary to the reported studies reviewed for present work. The studies of Balani et al, Bakshi et al, and Franca et al, has reported PPV of 100% due to low false positive cases.…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…19 A report of Reddy et al, has reported low PPV of 58.8%. 12 These values are contrary to the reported studies reviewed for present work. The studies of Balani et al, Bakshi et al, and Franca et al, has reported PPV of 100% due to low false positive cases.…”
Section: Resultscontrasting
confidence: 89%
“…7 The literature reviewed for present study have commented on wide discordance between clinical diagnosis and ultrasonography as necessitating the FNAC of SOL of liver that would result in the mismanagement of sizeable number of patients. The present study recorded 25 discordant diagnosis when clinical diagnosis is compared with that of USG findings which is similar to observation made by Patel et al, and Sudhakar et al 8,10 The utility of cell block of aspirates of SOL of FNAs as paraffin block for histological assessment of SOL has been quoted to be useful and worthy in the studies of Singh et al, Goel et al, Reddy et al, and Sukumaran et al 3,5,11,12 The present study made a similar observation about utility of cell block of needle aspirates to achieve tissue diagnosis for comparison with cytodiagnosis.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Findings of present study are comparable with Munnaza, Asghar C M Swamy, and Hemlatha. 6,[8][9][10] In this study, no fatal or severe complications were noted which may be attributed to complete pre-aspiration work up and careful choice of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[15] In the present study population, no complications occurred during and after the procedure. The incidence of needle track seedling was 0.6% (one of 148 patients of HCC) in study done by Reddy et al [16] Among the 13 cases of ovarian masses, most common lesions were malignant (eight cases, 61.54%); a similar observation was made out in the study done by Sobha et al [17] (58.3%) and Pranab et al [18] (87.5%), which was different from the observation made by Sidhalingreddy and Andola. [4] In their study, benign lesions were more common and most of them were cystadenomas.…”
Section: Discussionmentioning
confidence: 99%